Keterkaitan Antara Pelaksanaan Prinsip Mengenali Pengguna Jasa Oleh Notaris Dengan Rahasia Jabatan Notaris - Maulina, Kezia Tiffany (Dinasti Research, 2025)
This research discusses the obligations of Notaries to implement the Principle of Recognizing Service Users which is related to the confidentiality of positions which must be carried out by Notaries. Implementation of the Principle of Recognizing Service Users is one of the efforts made by the Indonesian government to eradicate and handle the crime of money laundering and the crime of financing terrorism, which is carried out by reporting parties to the Center for Financial Transaction Reporting and Analysis, one of which is a Notary. However, this creates confusion for Notaries because on the one hand, Notaries must carry out their obligations by submitting reports to the Financial Transaction Reports and Analysis Center, but on the other hand, Notaries must carry out the confidentiality of their position, namely maintaining the confidentiality of the information required when making a deed. The problem raised in this research is regarding the relationship between the application of the Principle of Recognizing Service Users by Notaries and the confidentiality of positions that must be carried out by Notaries. The research method used to answer this problem is a doctrinal research method that is descriptive-analytical in nature. The results of the research found that the relationship between the application of the Principle of Getting to Know Service Users by Notaries and the confidentiality of positions that are required to be carried out by Notaries is not contradictory. This is because the reporting procedure to the Financial Transaction Reports and Analysis Center by the Notary is carried out in the context of implementing statutory regulations, so this is an exception to the Notary's obligation to keep confidential the information he obtains for the purposes of making a deed. Therefore, researchers provide suggestions for Notaries to study more deeply the application of the Principles of Recognizing Service Users and the need to confirm that the application of the Principles of Recognizing Service Users does not conflict with the Notary's obligation to maintain confidentiality.